Influence of boron on yield and grain quality of pearl millet (Pennisetum glaucum) - SINHA, PRATIMA; CHATTERJEE, CHITRALEKHA (The Indian Journal of Agricultural Sciences, 2013)
An experiment Was conducted during the rainy season of 1991 to study the effect of 7 concentrations of boron on 'WCC 75' pearl millet [Penniselum glauecum (L.) R. Br. emend. Stuntz]. Boron@ 0.33 mg/litre gave the highest weight of inflorescence (69.8 g/plant). grain yield (50.9 g/plant). 100-grain weight (1.0g) and biomass (117.1 g/plant). However, deficient or excess supply orB application adversely affected these characters. Its deficiency decreased the grain yield (1.3 g/plant) compared With its excess supply (19.0 g/plant) and the effect was more marked (In grain yield than on biomass. B @ 0.66 mg/litre resulted in a minimum phenol (0.008%) and nitrate-N (0.10%) in the grain. which increased under its deficient (< 0.33 mg/litre) or eXcess (> 0.66 mg/litre) supply. Though B decreased the concencration of protein (6.48 and9.25%) and starch. (5.87 and 6.52%) hoth at low as well as excess supply. at former level it had a greater accumulation of sugars (0.352%) compared with that at the latter level (0.194%). An increase in B supply increased its content in grain; however this increase was much less (3 g/g dry weight) than that in the leaves. Its deficiency of excess symptoms were apparent on young leaves under low (6.5 g/g dry matter) or excess (268 g/g dry matter) content of B.